Dictionary of pharmacovigilance - Alghabban, Amer. (London ; Chicago : Pharmaceutical Press, 2004)
Pharmacovigilance is the process of monitoring the use of medicines to identify previously unrecognized adverse drug reactions thereby assessing their risk/benefit balance. This dictionary contains a list of abbreviations, terms and phrases giving definitions of pharmacovigilance terms
Includes bibliographical references.
Keywords: Drugs -- Side effects -- Dictionaries; Pharmacoepidemiology -- Dictionary -- English; Drug Monitoring -- Dictionary -- English; Drug and Narcotic Control -- Dictionary -- English; Pharmaceutical Preparations -- adverse effects -- Dictionary -- English; Product Surveillance, Postmarketing -- Dictionary -- English